2010
DOI: 10.1177/0894845309358999
|View full text |Cite
|
Sign up to set email alerts
|

Future Plans of Urban Youth: Influences, Perceived Barriers, and Coping Strategies

Abstract: This study examines the academic and career goals set by urban youth as well as their perceived career barriers and the strategies they anticipate using to face these barriers. Nine adolescents in the 11th and 12th grades from two large, urban public schools in the Midwest were interviewed for this study. Students’ responses were analyzed using the consensual qualitative research method developed by Hill and colleagues. Seven domains were identified in participant responses, addressing participant ideas about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Studies also found that the school systems of the research participants' colleges were not concerned with the cosmetology-related majors and the curriculums. Whereas, cosmetology careers influence refers to individual's self-knowledge and skills to sustain in their profession [28]. In addition, [26] also affirm that practical training was very helpful in student's prior preparation for work for them to gain knowledge and firm their skills.…”
Section: Results Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…Studies also found that the school systems of the research participants' colleges were not concerned with the cosmetology-related majors and the curriculums. Whereas, cosmetology careers influence refers to individual's self-knowledge and skills to sustain in their profession [28]. In addition, [26] also affirm that practical training was very helpful in student's prior preparation for work for them to gain knowledge and firm their skills.…”
Section: Results Analysismentioning
confidence: 93%
“…There are nine studies focused on Korean cosmetology field [19]; [20]; [21]; [22]; [23]; [24]; [25]; [26]; [27]. Other than that, each study examined Pakistan cosmetology field [12], Midwest cosmetology field [28], Netherlands cosmetology field [11], Turkey cosmetology field [1], Taiwan cosmetology field [29] and Ghana cosmetology field were also included in this review.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The powerful role of adult expectations cannot be overstated. Numerous studies have identified both teacher and parental expectations as critical in the academic outcomes of youth (Howard et al, 2010). As an example, in a study that compared teachers’ ratings on student characteristics (e.g., attitudes toward schoolwork, relationships with peers) for teachers with high expectations (HiEx) for all of their students versus teachers with low expectations (LoEx) for all of their students, differing patterns of correlations were found between teacher groups.…”
Section: Multifinalitymentioning
confidence: 99%
“…Specifically, Constantine, Erickson, Banks, and Timberlake (1998) described the dangerous role that racial discrimination and stereotyping have played in creating self‐fulfilling prophecies for urban minority youth, inhibiting their academic and occupational aspirations and subsequent achievement. Furthermore, racial prejudice and discrimination, financial problems, low self‐efficacy, and lack of opportunities challenge the academic or career goal setting of urban minority youth, rendering career interventions that focus on career goal setting essential (Howard et al, 2010).…”
Section: Work Hopementioning
confidence: 99%